Prohibition of Child pornography: Enhancing Child Protection in Indonesia - Zendy Wulan Ayu Widhi Prameswari (Yuridika, 2020)
As many other countries in the world, Indonesia has serious problems with child pornography. The problems linked with the child pornography exist in Indonesia, involving both male and female children. In 2008, Law Number 44/2008 on Pornography was enacted. With regard to the widespread distribution and accessibility of child pornography through the Internet, Indonesia also has Law Number 11/2008 and its revision on Electronic Information and Transaction. At the international level, Indonesia has ratified the Convention on the Rights of the Child (CRC). Furthermore, in 2012, Indonesia ratified the Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography (OPSC). However, based on data from the Indonesian Child Protection Commission (Komisi Perlindungan Anak Indonesia/KPAI) from 2011 to 2016 there were 1709 cases of child pornography and cybercrime. The cases of child pornography are still increasing and seems impossible to stop. This paper will scrutinize how the existing Indonesian law concerning prohibition of child pornography protects the children. It will also examine whether the law are in compliance with the OPSC. This paper is a doctrinal research using statute, conceptual and comparative approaches. The existing Indonesian law will be compared with the OPSC. The study will show some of the compatibility issues of Indonesian respective national law with the OPSC. On the basis of the findings, the last part of the study will provide recommendations on how Indonesia shall enhance the fight against child pornography.